Preparation of copper-doped TiO₂ photocatalyst for dye degradation under UV light (effect on incubation temperature): article / Nor Atikah Jembari, Lim Ying Pei and Lim Ying Chin - Jembari, Nor Atikah; Lim, Ying Pei; Lim, Ying Chin (2017)
The objective of this study was to investigate the preparation of hybrid CuO/TiO₂ photocatalyst by using wet impregnation method at different incubation temperature. The physical characterization of the photocatalyst was performed using X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), Field Emission Scanning Electron Microscope (FESEM) and Brunauer-Emmett-Teller (BET). The photocatalytic activity of Methyl Orange was analyzed by determine the percentage degradation of Methyl Orange under uv light irradiation. The observed results of photocatalytic activity suggest that the incubation temperature of 50 °C is the optimum as the percentage degradation is the highest which is 82.06 %. From the characterization analysis, the copper elements cannot be detected in XRD analysis. The anatase peak at 2Ѳ show TiO₂ only peak after incorporated with different incubation temperature. In the EDX analysis, the CuO can be detected in the EDX mapping for hybrid CuO/TiO₂ photocatalyst, before and after degradation. The surface area of hybrid CuO/ TiO₂ photocatalyst, before and after degradation are higher than bare TiO₂ which are 8.8137m²/g and 9.7521 m²/g while for bare TiO₂ is 2.0801 m²/g. Among the incubation temperature, the photocatalyts that synthesized at 50 °C has the best uv light response and the highest photodegradation activity.